Population Differentiation and Demographic History of the Cycas taiwaniana Complex (Cycadaceae) Endemic to South China as Indicated by DNA Sequences and Microsatellite Markers - Wang, Xin-Hui; Li, Jie; Zhang, Li-Min; He, Zi-Wen; Mei, Qi-Ming; Gong, Xun; Jian, Shu-Guang (Frontiers in Genetics, 2019)
Historical geology, climatic oscillations, and seed dispersal capabilities are thought to influence the population dynamics and genetics of plants, especially for distribution-restricted and threatened species. Investigating the genetic resources within and among taxa is a prerequisite for conservation management. The Cycas taiwaniana complex consists of six endangered species that are endemic to South China. In this study, we investigated the relationship between phylogeographic history and the genetic structure of the C. taiwaniana complex. To estimate the phylogeographic history of the complex, we assessed the genetic structure and divergence time, and performed phylogenetic and demographic historical analyses. Two chloroplast DNA intergenic regions (cpDNA), two single-copy nuclear genes (SCNGs), and six microsatellite loci (SSR) were sequenced for 18 populations. The SCNG data indicated a high genetic diversity within populations, a low genetic diversity among populations, and significant genetic differentiation among populations. Significant phylogeographical structure was detected. Structure and phylogenetic analyses both revealed that the 18 populations of the C. taiwaniana complex have two main lineages, which were estimated to diverge in the Middle Pleistocene. We propose that C. fairylakea was incorporated into C. szechuanensis and that the other populations, which are mainly located on Hainan island, merged into one lineage. Bayesian Skyline Plot analyses revealed that the C. taiwaniana complex experienced a recent decline, suggesting that the complex probably experienced a bottleneck event. We infer that the genetic structure of the C. taiwaniana complex has been affected by Pleistocene climate shifts, sea-level oscillations, and human activities. In addition to providing new insights into the evolutionary legacy of the genus, the genetic characterizations will be useful for the conservation of Cycas species.